El aprendizaje de la lectura y escritura en la Escuela Infantil. - Corral Villacastín, A.Mª (Didáctica. Lengua y Literatura, 1997)
It is a fact that children can learn to read before they are six years oíd; therefore, not only speaking, but also reading --and writing-- should be treated as integral elements of a communication process.
Keywords: Reading; precoclaus learning; reading rna¡turity; methodology LOCSE